Analysis of Lead (Pb), Zinc (Zn), and Copper (Cu) Levels in Skipjack Tuna (Euthynnus affinis) Using Atomic Absorption Spectrophotometry - Subardi Bali; Deri Islami (Jurnal Ilmu Kesehatan Abdurrab, 2025)
Heavy metals are elements with high density that are toxic at certain concentrations and cannot be naturally degraded, making them prone to accumulation in marine organisms. Exposure to heavy metals through the consumption of contaminated fish can cause adverse health effects, such as neurological disorders, organ damage, and impaired physiological functions. This study aimed to determine the levels of lead (Pb), zinc (Zn), and copper (Cu) in skipjack tuna (Euthynnus affinis) from the coastal waters of West Sumatra and compare them with the maximum limits for heavy metal contamination in food as regulated by the Indonesian Food and Drug Authority (BPOM Decree No. 03725/BSK/VII/1989). Samples were collected from three locations: Pesisir Selatan, Pasaman, and Pariaman. Sample preparation was carried out through wet digestion using a microwave digester to optimally dissolve the metals, followed by analysis with Atomic Absorption Spectrophotometry (AAS) at specific wavelengths for each metal. The results showed that skipjack tuna from Pesisir Selatan, Pasaman dan Pariaman Pb at ,230 mg/kg, 0,525 mg/kg, and 0,251 mg/kg. seng (Zn) 0,113 mg/kg, 0,101 mg/kg and 0,129 mg/kg,(Cu) 0,492 mg/kg 0,379 mg/kg, and 0,466 mg/kg. All detected levels were well below the BPOM maximum permissible limits of 2.0 mg/kg for Pb , 100 mg/kg for Zn, and 20 mg/kg for Cu. Therefore, skipjack tuna from all three sampling sites are considered safe for consumption in terms of heavy metal contamination, according to the applicable national standards.